Analysis of the Impact of Efficiency and Budget Cuts on the Treasurer’s Inventory Money of the Directorate General of Dukcapil of the Ministry of Home Affairs - Kadir, Abdul; Silvia, Silvia; Trasviyanti, Selvi; Sugiyanto, Sugiyanto (The Future of Education Journal, 2026)
This study examines the impact of efficiency policies and budget cuts on the management of the treasurer’s inventory money at the Directorate General of Population and Civil Registration (Dukcapil) of the Ministry of Home Affairs. The implementation of government efficiency measures and fiscal tightening has raised concerns regarding the flexibility and effectiveness of inventory money in supporting daily operational activities. The purpose of this research is to analyze how efficiency and budget reduction policies affect planning, utilization, control, and accountability of the treasurer’s inventory money. This study employs a qualitative research method using in-depth interviews with relevant officials, analysis of financial and administrative documents, and direct observation to obtain a comprehensive understanding of the phenomenon. The results show that efficiency policies and budget cuts lead to reduced flexibility in fund utilization, increased administrative burden for treasurers, and the need for adjustments in financial management practices. Although these policies strengthen financial discipline and accountability, they also create challenges in responding to urgent operational needs and maintaining service performance. The study concludes that effective management of treasurer’s inventory money under efficiency and budget cut policies requires adaptive strategies, improved coordination, and clear regulatory guidance to ensure public service delivery remains effective while upholding principles of transparency and accountability.